2017
DOI: 10.1002/jcc.25090
|View full text |Cite
|
Sign up to set email alerts
|

Molecular acidity: An accurate description with information‐theoretic approach in density functional reactivity theory

Abstract: Molecular acidity is one of the important physiochemical properties of a molecular system, yet its accurate calculation and prediction are still an unresolved problem in the literature. In this work, we propose to make use of the quantities from the information-theoretic (IT) approach in density functional reactivity theory and provide an accurate description of molecular acidity from a completely new perspective. To illustrate our point, five different categories of acidic series, singly and doubly substitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 70 publications
4
56
0
Order By: Relevance
“…We previously proposed to use two equivalent descriptors, MEP (molecular electrostatic potential) and NAO (natural atomic orbital), for the purpose . Our more recent studies using ITA quantities indicated that better results could be obtained. In one of our recent studies shown in Figure , five different categories of acidic series were investigated, accurate descriptions to simultaneously simulate all data sets, a total of 95 points, have been accomplished, with the correlation coefficient better than 0.96.…”
Section: Recent Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously proposed to use two equivalent descriptors, MEP (molecular electrostatic potential) and NAO (natural atomic orbital), for the purpose . Our more recent studies using ITA quantities indicated that better results could be obtained. In one of our recent studies shown in Figure , five different categories of acidic series were investigated, accurate descriptions to simultaneously simulate all data sets, a total of 95 points, have been accomplished, with the correlation coefficient better than 0.96.…”
Section: Recent Applicationsmentioning
confidence: 99%
“…Comparisons of experimental p K a data of all five series of compounds with the fitted p K a data using five ITA quantities from (a) the acidic atom and (b) the leaving proton. (Reprinted with permission from Reference . Copyright 2017 John Wiley & Sons)…”
Section: Recent Applicationsmentioning
confidence: 99%
“…However, there are many options to express the relations defined in Equations and explicitly. Following earlier suggestions in the field the linear combination form of information theoretic quantities has been considered, though other cases are also possible which their applicability may be examined elsewhere. Therefore, the working expressions employed in our calculations take the below forms, P0.12em[]ρ=jcjQj P0.12em[]ρ=jcjQj+cneVne where the summations run over information theoretic quantities Q j and c j and c ne are the expansion coefficients to be determined by the least squares fitting procedure.…”
Section: Theoretical and Computational Basicsmentioning
confidence: 99%
“…Onicescu information energy of order n , EOn, EOn[]ρ=1n1ρrndboldr1em()n2 and Ghosh–Berkowitz–Parr (GBP) entropy, S GBP , SGBP[]ρ=32italickρ0.12em()0.12emboldr0.34em[]c+lnt();rρtTF();rρ0.24emdboldr where ρ ( r ) is the ground state electron density of an N ‐electron system which satisfies the normalization condition ∫ ρ ( r ) d r = N and ∇ρ ( r ) is the density gradient. In the Onicescu information energy formula, Equation , the options of n = 2and n = 3 are often employed, though other cases are also possible . Moreover, in the relation of GBP entropy, Equation , k is the Boltzmann constant, c=53+ln4normalπ0.1emck3, t ( r ; ρ ) is the kinetic energy density which is related to the total kinetic energy T S via ∫ t ( r ; ρ ) d r = T S , and t TF ( r ; ρ ) is the Thomas–Fermi kinetic energy density given by t TF ( r ; ρ ) = c k [ ρ ( r )] 5/3 with ck=3103normalπ22/3.…”
Section: Theoretical and Computational Basicsmentioning
confidence: 99%
See 1 more Smart Citation